2012
DOI: 10.1121/1.4747618
|View full text |Cite
|
Sign up to set email alerts
|

Phonation threshold pressure and the elastic shear modulus: Comparison of two-mass model calculations with experiments

Abstract: Ishizaka and Flanagan's classic two-mass model of vocal fold motion is applied to small oscillations where the equations become linear and the aerodynamic driving force is described by an effective stiffness. The solution of these equations includes an analytic formula for the two eigenfrequencies; this shows that conjugate imaginary parts of the frequencies emerge beyond eigenvalue synchronization and that one of the imaginary parts becomes zero at a pressure signaling the instability associated with the onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Studies with physical models (Titze et al, 1995;Chan et al, 1997;Mau et al, 2011;Mendelsohn and Zhang, 2011), computer simulation models (Pickup and Thomson, 2011), and analytical calculations (Titze, 1988b;Lucero, 1998;Chan and Titze, 2006;Klemuk et al, 2010;Lucero et al, 2011;Fulcher et al, 2012) have shown that a near rectangular glottis (as viewed in the coronal plane) produces the lowest oscillation threshold pressure. (Direct measurement of this configuration in human subjects has not been reported.)…”
Section: A Criterion For Optimal Adductionmentioning
confidence: 99%
“…Studies with physical models (Titze et al, 1995;Chan et al, 1997;Mau et al, 2011;Mendelsohn and Zhang, 2011), computer simulation models (Pickup and Thomson, 2011), and analytical calculations (Titze, 1988b;Lucero, 1998;Chan and Titze, 2006;Klemuk et al, 2010;Lucero et al, 2011;Fulcher et al, 2012) have shown that a near rectangular glottis (as viewed in the coronal plane) produces the lowest oscillation threshold pressure. (Direct measurement of this configuration in human subjects has not been reported.)…”
Section: A Criterion For Optimal Adductionmentioning
confidence: 99%